Release of outer membrane fragments by exponentially growing Brucella melitensis cells. - Gamazo, C (1987)
Rough and smooth strains of Brucella melitensis released a membranous material that was devoid of detectable NADH oxidase and succinic dehydrogenase activity (cytoplasmic membrane markers) but that contained lipopolysaccharide, proteins, and phospholipids. This material was composed of two fractions that had similar chemical compositions but that were of different sizes which were separated by differential ultracentrifugation. Electron microscopy showed that both fractions are made of unit membrane structures. The membrane fragments were released during the exponential phase of growth, and no leakage of malic dehydrogenase activity (cytosol marker) was detected. Thus, the fragments were unlikely a result of cell lysis. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot analysis showed that, although group 2 Brucella outer membrane proteins and lipoprotein were not detected, the proteins in the membranous material were outer membrane proteins. Gas-liquid chromatography analysis showed a similar fatty acid profile for the cell envelope and the outer membrane fragments of the smooth strain B. melitensis 16M. In contrast, the outer membrane fragments from the rough 115 strain were enriched in palmitic and stearic acids. With respect to the unfractionated cell envelope, outer membrane fragments were enriched in phosphatidylcholine, a phospholipid that is unusual in bacterial membranes.